The Effect of Human Resource Skills and Capabilities on SMEs Performance - Reni Wijaya; DORRIS Yadewani; Kurniati Karim (International Journal of Islamic Business and Management Review, 2022)
This study aims to investigate more deeply the impact of skills and abilities on the performance of Small and Medium Enterprises in Kota Pariaman. The population of this research is 4,281 Small and Medium Enterprises located in Pariaman City where the number of samples is 98 SMEs. The technique used in collecting data for this research is to use Field Research, then the technical data analysis used is factor analysis. Hypothesis testing is carried out using Statistical Program Social Scence (SPSS) 24.0 for Windows by using factor analysis, among others instrument test, classical assumption test, Goodness of Fit test, multiple linear regression analysis. The results of this study indicate that a) There is a positive influence of skills on the performance of small and medium enterprises of 13.2%. b) There is a positive effect of ability on the performance of small and medium enterprises of 30.8%. c) There is a positive influence of skills and abilities on the performance of small and medium enterprises of 34.1%.